2003
DOI: 10.1080/00365540310000274
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years of Extrapulmonary Tuberculosis in a Danish University Clinic

Abstract: The objective of this study was to describe the symptoms, diagnostic measures and outcomes of extrapulmonary tuberculosis (ex-TB) in a Danish university clinic from 1990 to 1999. 48 patients with ex-TB were identified retrospectively and clinical and laboratory data extracted from the patient files. The majority were immigrants from Africa (71%). A direct connection between symptoms on admission and anatomical localization of TB was found in 83%. The main localizations of ex-TB were peripheral lymph nodes (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
3
12
0
1
Order By: Relevance
“…In Western countries, these are the preferred systems for TB culture; however, in India, most centers prefer the traditional culture medium. Culture yield in this study using the BACTEC 460TB are comparable to studies in small samples of patients with abdominal tuberculosis in the developed countries [6][7][8]. The yield with the LJ medium is comparable to the previously reported studies from India [1,9].…”
Section: Discussionsupporting
confidence: 88%
“…In Western countries, these are the preferred systems for TB culture; however, in India, most centers prefer the traditional culture medium. Culture yield in this study using the BACTEC 460TB are comparable to studies in small samples of patients with abdominal tuberculosis in the developed countries [6][7][8]. The yield with the LJ medium is comparable to the previously reported studies from India [1,9].…”
Section: Discussionsupporting
confidence: 88%
“…21 Moreover, patients of foreign origins had most EPTB cases, and approximately two-thirds of all patients with EPTB were immigrants, approximately half from Somalia. 20,22 In addition, similar to the situation in Denmark, the incidence of TB in Greenland had doubled from 1990 to 1997. 23 This study was conducted to assess age, sex, and origin specific risk and categories of EPTB (involving a specific anatomic site) in a large cohort of TB patients that are believed to be diagnosed by using the same diagnostic standards.…”
Section: Introductionmentioning
confidence: 82%
“…Many studies of extrapulmonary tuberculosis [6,7,9,14,16 Á20] have shown a female preponderance, although in some studies the sex distribution has been more even [5,12,13,15,21]. In our study 44 of the 63 patients were female and 19 male.…”
Section: Discussionmentioning
confidence: 45%
“…The most common form of tuberculosis is pulmonary tuberculosis, which accounted for 67.7% of all patients with tuberculosis in Finland in 2004 [2]. Tuberculous lymphadenitis has been reported as the most common form of extrapulmonary tuberculosis in many studies [3], although in some studies other locations have been found to be more common [4,5]. Lymphadenitis is also the most common form of tuberculosis in the head and neck Á other locations are rare [6,7].…”
Section: Introductionmentioning
confidence: 98%